Comparison of ultra-short race pace and high-intensity interval training in age group competitive swimmers - Papadimitriou, K.; Kabasakalis, A.; Papadopoulos, A.; Mavridis, G.; Tsalis, G. (Sports, 2023)
The aim of this study was to examine the acute responses to an Ultra-Short Race Pace Training (USRPT) and a High-Intensity Interval Training (HIIT), both oriented for the event of 100 m freestyle. Eighteen national-level swimmers (8 boys, 10 girls) aged 13.5 ± 0.1 years, with 8.0 ± 0.5 years of experience participated in the study. All participants completed a USRPT and a HIIT protocol consisting of 2 × 10 × 25 m (USRPT1 & USRPT2) and 5 × 50 m. Significantly higher swimming velocity (SV) were achieved in USRPT compared to HIIT (p < 0.001), while significantly lower distance per stroke (DPS) and stroke index (SI) were obtained (p = 0.007 and p < 0.001). Also, significantly lower blood lactate and glucose (BL & BG) concentrations were found after USRPT (p = 0.001 and p = 0.037). Heart rate (HR) and rate of perceived exertion (RPE) were significantly lower after USRPT than HIIT (p < 0.001 and p = 0.015). According to the results, an USRPT swimming set consisting of 20 × 25 m at a 100 m pace seems to induce more specific responses in kinematic characteristics, biomarkers, HR and RPE compared to a 5 × 50 m HIIT set.